THE JESUS GENEALOGY CONTROVERSY REVEALS THE SECRET OF THE SALVATION PLAN: The Presence of Foreign and Sinful Women in The Genealogy of Jesus Christ Based on Matthew 1:1–17 - Janes Sinaga; Juita Lusiana Sinambela; Gerbin Tamba; Exson Eduaman Pane (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2022)
This study aims to uncover the secret of the plan of salvation that lies in the genealogy of Jesus Christ recorded in Matthew 1:1–17, especially in the context of the presence of foreign and sinful women in Jesus' lineage. In this effort, the method of theological analysis was used to understand the theological significance and moral message contained in the inclusion of women such as Tamar, Rahab, Ruth, and Uriah's wife in the genealogy of Christ. This research delves into the historical and cultural context of Matthew's writing and analyzes how the inclusion of these women complements and illustrates the fulfillment of God's all-encompassing and gracious promise. The findings of this study will deepen understanding of the redemptive narrative woven into the genealogy of Jesus Christ, provide deep insight into the inclusiveness of God's plan of salvation, and offer an evocative testimony of His infinite love and mercy to all mankind.